2020
DOI: 10.1108/el-12-2019-0294
|View full text |Cite
|
Sign up to set email alerts
|

Ensuring continued use of a digital library: a qualitative approach

Abstract: Purpose This paper aims to identify the factors affecting continued use of digital libraries in a military context. Design/methodology/approach Semi-structured interviews with four focus groups consisting of 21 respondents, who are military education instructors and librarians, were carried out. This qualitative approach study adopted content analysis methods that were designed to contrast and make comparisons based on the participants’ responses. The valid responses were analyzed using NVivo 12 Plus. Find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 51 publications
(63 reference statements)
0
4
0
Order By: Relevance
“…Option of customization should exist in digital software. Abdul Rahman and Mohezar (2020) identified the continued usage of digital content. It was shown that several changes had taken place in the present era due to technological innovations and librarians needed to embrace changes willingly otherwise other professionals could replace librarianship and libraries.…”
Section: Literature Analysismentioning
confidence: 99%
“…Option of customization should exist in digital software. Abdul Rahman and Mohezar (2020) identified the continued usage of digital content. It was shown that several changes had taken place in the present era due to technological innovations and librarians needed to embrace changes willingly otherwise other professionals could replace librarianship and libraries.…”
Section: Literature Analysismentioning
confidence: 99%
“…Rafique et al (2021), Rahman and Mohezar (2020) and Wang et al (2018a, 2018b) cited quality of information, people, digital literacy, retrieval skills, resource compatibility, user interface design and information as CSFs that affect behavioural intention to use the mobile library. Similarly, Liu et al (2020) highlighted social and technological factors as CSF in the development and usage of mobile DLs.…”
Section: Discussion Of Literature From the Tablementioning
confidence: 99%
“…According to [11], users' continuous desire to use a digital library is correlated with the perceived usefulness and the convenience of use of the WBLIS, which includes WebOPAC and electronic resources. In focus group interviews conducted to study the digital library (DL) system in the context of military education, the majority of respondents emphasized the need for providing sufficient information on each link to the library services on the DL system.…”
Section: Library Technologymentioning
confidence: 99%